Peran Guru Menurut Abdurrahman An-Nahlawi dan Relevansinya dengan Pendidikan Kontemporer - Fidina Choiru Darojah; Adinda Rizky Fadhila; Nais Nourma Nastiti; Enggal Bagas Nova Saputra; Rio Kurniawan (JURNAL PENDIDIKAN ISLAM AL I’TIBAR, 2024)
The purpose of this study is to find out how the role of teachers according to Abdurrahman an-Nahlawi and its relevance in contemporary education. This research was conducted using the library research method with primary data sources in the form of books, scientific articles, and other publications relevant to the subject. The findings of this study show that the role of teachers according to an-Nahlawi is the person responsible for shaping and developing all the potential of students and in line with Islamic values, this is very relevant to contemporary education, where teachers not only transfer knowledge but teachers also have responsibility for attitudes, knowledge, and skills. Teachers are also not only educators, but also facilitators, motivators, curriculum designers and compilers as well as evaluators.